Spatiotemporal Differences in Tectonic Deformation and Its Dynamic Mechanisms in the East China Sea Shelf Basin - Junlan Song; Yumao Pang; Chuansheng Yang; Yanqiu Yang; Luning Shang; Changqing Yang; Jing Sun (Journal of Ocean University of China, 2025)

Differences in Mesozoic–Cenozoic Structural Deformation Between the Northern and Southern Parts of the East China Sea Shelf Basin and Their Dynamic Mechanisms - Chuansheng Yang; Junlan Song; Yanqiu Yang; Luning Shang; Jing Liao; Yamei Zhou (Journal of Marine Science and Engineering, 2025)
The East China Sea Shelf Basin (ECSSB) and its adjacent areas, as key regions of the ocean–continent transition zone, have been affected by multiple complex plate collisions, subduction, and back-arc tension since the Mesozoic Era. The structural deformation provides a large amount of geological information on the ocean–continent transition zone. There are significant spatiotemporal differences in the structural deformation within the basin. However, the research remains insufficient and understanding is inconsistent, especially regarding the systematic study of the differences and dynamic mechanisms of north–south structural deformation, which is relatively lacking. This study is based on two-dimensional multi-channel deep reflection seismic profiles spanning the southern and northern basin. Through an integrated re-analysis of gravity, magnetic, and OBS data, the deformation characteristics and processes of the Meso-Cenozoic structures in the basin are analyzed. The differences in structural deformation between the southern and northern basin are summarized, and the controlling effects of deep crust–mantle activity and the influencing factors of shallow structural deformation are explored. Based on deep reflection seismic profiles, the structural deformation characteristics of the Yushan–Kume fault are revealed for the first time, and it is proposed that NW faults, represented by the Yushan–Kume fault, have important tuning effects on the north–south structural differential deformation in the ECSSB. The thermal subsidence of the lithosphere is the direct cause of the development of the Mesozoic ECSSB, while the subduction of the Paleo-Pacific plate is one of the important factors contributing to it. The combined effect of the two has led to significant differences between the northern and southern Mesozoic basin. During the Cenozoic Era, the alternating subduction and changes in the direction of subduction of the Pacific Plate led to spatiotemporal differences in structural deformation within the ECSSB. The development of NW faults was a key factor in the differences in structural deformation between the northern and southern basin. The study of structural deformation differences in the ECSSB not only deepens our understanding of the tectonic evolution in the East Asian continental margin region, but also has important significance for the exploration and evaluation of deep hydrocarbon resources in the ECSSB.

Intraoceanic active rifting revealed by deep seismic reflection imaging in the southern Bay of Bengal, northeastern Indian Ocean - Luning Shang; Gang Hu; Thomas P. Ferrand; Jun Pan; Chuansheng Yang (Earth and Planetary Science Letters, 2025)

Refining the final phase of the seafloor spreading process in the West Philippine Basin through the recalibration of magnetic isochrones - Luning Shang; Hailong Li; Kai Lu; Panfeng Li; Gang Hu; Yong Zhang; Yongjian Yao; Chuansheng Yang (Tectonophysics, 2024)

Origin of the southern Ryukyu Forearc Terrace: A seaward-protrusion of arc crust elevated by subducted asperities? - Luning Shang; Gang Hu; Yongtao Chen; Chuansheng Yang; Yong Zhang (Journal of Asian Earth Sciences, 2023)

New magnetic data of the southern East China Sea and some geological interpretations - Luning Shang; Xunhua Zhang; Runlin Du; Yonggang Jia; Zhenxing Tian; Bo Han; Chuansheng Yang (Studia Geophysica et Geodaetica, 2016)

On the tectonic problems of the southern East China Sea and adjacent regions: Evidence from gravity and magnetic data - Luning Shang; Xunhua Zhang; Bo Han; Runlin Du (Journal of Ocean University of China, 2016)